AI-Driven Cloud Optimization: Leveraging Machine Learning to Enhance Cloud Performance - Sreelakshmi Somalraju, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
AI-driven cloud optimization transforms how organizations manage their cloud computing resources by employing sophisticated machine learning algorithms to analyze operational data and automate decision-making processes. As cloud environments grow increasingly complex across multiple providers and regions, traditional manual management approaches become insufficient, leading to inefficiencies and cost overruns. Machine learning techniques, including reinforcement learning, time series analysis, and clustering, enable intelligent resource allocation, cost reduction, performance enhancement, and proactive security management. The implementation architecture integrates data collection layers, analytics engines, automation frameworks, feedback loops, and governance controls to create self-improving systems. Despite compelling benefits, organizations face challenges in data quality and quantity, model training expertise, and change management during implementation. Future trends point toward multi-cloud optimization capabilities, edge-cloud coordination for distributed computing, and self-healing infrastructure that automatically remedies failures before they impact users.
Keywords: Cloud Computing Optimization; Artificial Intelligence; Machine Learning; Resource Allocation; Self-Healing Infrastructure